2021
DOI: 10.1371/journal.pntd.0008879
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing non severe cases of dengue from COVID-19 in the context of co-epidemics: A cohort study in a SARS-CoV-2 testing center on Reunion island

Abstract: Background As coronavirus 2019 (COVID-19) is spreading globally, several countries are handling dengue epidemics. As both infections are deemed to share similarities at presentation, it would be useful to distinguish COVID-19 from dengue in the context of co-epidemics. Hence, we performed a retrospective cohort study to identify predictors of both infections. Methodology/Principal findings All the subjects suspected of COVID-19 between March 23 and May 10, 2020, were screened for COVID-19 within the testing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…In addition, a false‐positive serology for dengue has been noted in patients with confirmed COVID‐19. 23 , 24 In a study in adults, Joubert et al 25 have observed that nonsevere dengue cases were more symptomatic than mild to moderate COVID-19. Body aches, headache, and retro-orbital pain were the presentations in dengue, whereas anosmia and delayed presentation (> 3 days post onset) were suggestive of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a false‐positive serology for dengue has been noted in patients with confirmed COVID‐19. 23 , 24 In a study in adults, Joubert et al 25 have observed that nonsevere dengue cases were more symptomatic than mild to moderate COVID-19. Body aches, headache, and retro-orbital pain were the presentations in dengue, whereas anosmia and delayed presentation (> 3 days post onset) were suggestive of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers underlined the difficulties in distinguishing the non-severe case of Dengue from COVID-19 in dengue epidemic regions. [ 18 ] Another recent piece of evidence highlighted the need for the adoption of a rapid strategy to prevent a possible outbreak of dengue during the COVID-19 pandemic in Bangladesh. [ 11 ] Here we report a case of heterozygous beta-thalassemia (previously undiagnosed) or beta-thalassemia trait, coinfected with COVID-19 and dengue fever simultaneously and well managed at the COVID-19 unit of icddr,b.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that patients with high levels of Ud-OPN are not likely to suffer from COVID-19. These findings may also explain why non-severe forms of dengue are more symptomatic than COVID-19 [164]. However, it might be early to conclude that the titers of Ud-OPN can differentiate DF, CV, or CP, because DF, DHF, and leptospirosis patients were from Manila in the Philippines, while the CV and CP patients were from Sendai, Japan.…”
Section: Coronavirus Disease 2019 (Covid-19)mentioning
confidence: 99%
“…Body ache, headache, and retro-orbital pain were indicative of dengue, whereas contact with a COVID-19-positive case, anosmia, delayed presentation (>3 days post-symptom onset), and the absence of active smoking were indicative of COVID-19. Based on the study, basic clinical and epidemiological indicators may help distinguish COVID-19 and dengue from each other and other febrile illnesses [164].…”
Section: Coronavirus Disease 2019 (Covid-19)mentioning
confidence: 99%